Phenomenological Insights into Children's Experiences: The Transition to Preschool - See, Yih Wern; Zahari, Ishak; Nazri, Abdul Rahman Mohd (EDUCARE: Journal of Primary Education, 2024)
Children’s transition to preschool has significant theoretical implications, especially regarding the expectations formed by parents and teachers, which often raise concerns. This qualitative study used a case study to explore the transition of preschool children in Malaysia, focusing on forming social relationships. The research methodology involved observation, interviews, and photography over eight weeks, highlighting the importance of listening and understanding children’s voices to support their social and emotional adaptation to a new environment. The results showed that rules and routines played a significant role in helping children adapt to preschool, contributing significantly to their academic, social, and cognitive development. The transition process was enriched by event-based activities such as birthday parties, which were fun and important in teaching social skills through collaboration and shared celebration. This study highlights the importance of designing child-centered educational activities that educate, inspire, and engage children, helping them feel valued and an integral part of their preschool community. The findings of this study make an important contribution to understanding how rules and routines in preschools can facilitate children’s adaptation and significantly impact their academic, social, and cognitive development. Furthermore, the study revealed that event-based activities, such as birthday parties, are fun and crucial in developing children’s social skills through collaborative activities and shared celebrations. This study emphasizes the importance of designing child-centered educational activities that inspire and actively engage children, making them feel valued and an integral part of their preschool community.